Efisiensi Frontier Usahatani Bawang Merah di Kecamatan Anggeraja Kabupaten Enrekang Provinsi Sulawesi Selatan - Eka Mulyana Murgas; Mohammad Natsir; Firmansyah Firmansyah (JURNAL AGRIBISNIS TERPADU, 2023)
This research was conducted to determine the efficiency of shallot farming in Saruran Village, Anggeraja District, Enrekang Regency. Researchers chose shallot farmers by 18% of the total population, so that 32 respondents were obtained as samples in this study. Sampling was carried out by simple random sampling, which is a simple random sampling method. Shallot farmers can provide more detailed information about shallot cultivation in Saruran Village. The data analysis technique used was quantitatively analyzed using multiple linear regression models and analyzed with the stochastic frontier to calculate the efficiency level of shallot farming. The results showed that the production factors of seeds, fertilizers, pesticides, and labor had a simultaneous effect on shallot production, while partially pesticides and labor had a significant effect on shallot production. The results of the technical efficiency analysis show that the mean efficiency is 0.740, meaning that it is more efficient in the use of its production factors because it is closer to 1. Keywords: Efficiency, Production, Shallots